PENGARUH APLIKASI QUIZIZ SEBAGAI ALAT PENILAIAN PEMBELAJARAN DI SEKOLAH DASAR - Humairoh, Siti; Imas Indah Mutiara; Hesti Widiastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning assessment process is an important component in an effort to obtain information on the learning outcomes that have been implemented. Assessment can also be used to determine the level of achievement of the material and the level of ability of students. The use of technology makes this process more interesting, fun and effective. The Quizizz application is a learning assessment media application that is expected to attract interest and increase students' concentration in learning assessment. This research aims to determine the effect of the quizizz application as a learning assessment tool in elementary schools. The subjects in this research were all fifth grade elementary school students. This type of research is qualitative research with a descriptive approach. Data collection uses interviews and observation. The results of this study show that using the Quizizz application as an assessment tool can foster competitiveness in learning because scores can be seen immediately so they can motivate students, questions can be done anywhere and teachers can monitor the progress of students' question paper work, questions also have an attractive appearance. These three aspects are the advantages of the quizizz application. Apart from these three aspects, this application makes it easier to work on questions, easy to use, develops creativity in learning, and makes it easier to collect test results. Based on the results of this research, the quiziz application can be used by teachers as a form of innovation in learning assessment, so that students will be more enthusiastic about learning and can improve student learning outcomes.